The state dependent impact of bank exposure on sovereign risk - Maximilian Podstawski; Anton Velinov (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The theoretical literature remains inconclusive on whether changes in bank exposure towards the domestic sovereign have an adverse effect on the sovereign risk position via a diabolic loop in the sovereign-bank nexus or reduce perceived default risk by acting as a disciplinary device for the sovereign. In this paper we empirically analyze the impact of exogenous changes in bank exposure on the risk position of the sovereign within a Markov switching structural vector autoregressive in heteroscedasticity (MSH-SVAR) framework for a set of EMU countries. We add to the methodological literature by allowing for regime dependent shock transmissions according to the volatility state of the financial system. Finding support for both, a stabilizing and a destabilizing effect, we document a clear clustering among the country sample: Rising bank exposure increased default risk for the EMU periphery, but decreased credit risk for the core EMU countries during times of financial stress.
Keywords: C32; E44; G10; 330; Markov-switching; heteroscedasticity; identification; sovereign-bank interlinkages; sovereign risk; credit default swap; contagion